Case Report: New genetic variant and widely different phenotypes observed in twins with Vanishing White Matter disease - Oron-Lexner, Ellis; Ditlev Larsen, Bjørk; Schelde-Olesen, Maria Therese (Frontiers in Pediatrics, 2025)
IntroductionVanishing White Matter disease (VWM) is a rare neurological disease, with an autosomal recessive inheritance. In this case report, we describe two four-year-old dizygotic twin brothers diagnosed with VWM with the same genotype and different phenotypes. We also describe a new likely pathogenic variant leading to VWM.MethodClinical examination, radiologic analysis and genetic workups, including whole genome sequencing and trio-genome analysis were conducted to diagnose and describe the patients' disease.ResultsA four-year-old boy was hospitalized with acute loss of motor functions and a somnolent state after a minor head trauma. Based on the clinical evaluation, radiological findings and genetic analysis he was diagnosed with VWM. The proband's twin carried identical pathogenic variants and exhibited white matter lesions on MRI. However, unlike the proband who presented with non-specific symptoms since the age of one, his twin remained asymptomatic at diagnosis.DiscussionThis case may indicate that factors other than genotype could affect the age of onset of VWM. During the genetic analysis a previously unknown genetic variant was detected, which is now classified as a likely pathogenic variant of VWM.